2012
DOI: 10.2139/ssrn.2103970
|View full text |Cite
|
Sign up to set email alerts
|

Coordination with Flexible Information Acquisition

Abstract: We study flexible information acquisition in a coordination game. "Flexible" acquisition means that players choose not only how much but also what kind of information to acquire. Information acquisition has a cost proportional to reduction of entropy. Hence, players will collect the information most relevant to their welfare but can be rationally inattentive to other aspects of the fundamental. When information is cheap, this flexibility enables players to acquire information that makes efficient coordination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 16 publications
0
57
0
Order By: Relevance
“…The mechanism it identifies is an important comparative static implication of the theory of rational inattention (Sims, 2003(Sims, , 2006Woodford, 2012Woodford, , 2014Martin, 2014;Caplin and Martin, 2014;Yang, 2014;Matějka and McKay, 2015; Caplin and Dean, 2015; see Caplin (forthcoming) for a review), and the experiment in section 5 is an explicit test thereof. The paper more generally relates to a theoretical literature on endogenous information acquisition by Bayesians (Caplin and Leahy, 2001;Bénabou andTirole, 2002, 2011;Suen, 2004;Koszegi, 2006;Eliaz and Spiegler, 2006;Gentzkow and Kamenica, 2011).…”
mentioning
confidence: 99%
“…The mechanism it identifies is an important comparative static implication of the theory of rational inattention (Sims, 2003(Sims, , 2006Woodford, 2012Woodford, , 2014Martin, 2014;Caplin and Martin, 2014;Yang, 2014;Matějka and McKay, 2015; Caplin and Dean, 2015; see Caplin (forthcoming) for a review), and the experiment in section 5 is an explicit test thereof. The paper more generally relates to a theoretical literature on endogenous information acquisition by Bayesians (Caplin and Leahy, 2001;Bénabou andTirole, 2002, 2011;Suen, 2004;Koszegi, 2006;Eliaz and Spiegler, 2006;Gentzkow and Kamenica, 2011).…”
mentioning
confidence: 99%
“…Second, the focus on the bias instead of the accuracy of information generates different, more general implications than previous works that posit information as unbiased noisy signals of some fundamental and focus on their optimal precision . The focus on bias, which is one of the qualitative properties of information, also connects with the growing literature on rational inattention and flexible information acquisition (e.g., Sims [, ], Yang []), whose main insight is that, to economize on the use of information, agents will focus on the information that is relevant to their welfare and be rationally inattentive to other aspects. This paper generates similar insights in an accounting setting.…”
Section: Introductionmentioning
confidence: 90%
“…In this respect, a natural question to ask is whether separation of sender's types becomes more likely under such a smooth or uncertain process. In general, the literature has shown that the information acquisition technology does matter for the selection of equilibria (see Yang, 2015 andDenti, 2016 for recent contributions on the issue). What we argue here is that the pooling outcome retains its prominence also when signal acquisition is not all-or-nothing or is not binary.…”
Section: Smooth Acquisition Costsmentioning
confidence: 99%